2010
DOI: 10.3748/wjg.v16.i18.2252
|View full text |Cite
|
Sign up to set email alerts
|

Expression of interleukin 6 in brain and colon of rats with TNBS-induced colitis

Abstract: These results revealed that changes in IL-6 expression in brain and colon tissues occur in different phases of IBD. Therefore, we propose that the nerve centre regulates and controls the occurrence and development of IBD via IL-6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 35 publications
2
21
0
Order By: Relevance
“…Rectal administration of TNBS resulted in the development of clinical symptoms of colitis, which manifested as a decrease in food intake and a decrease in body weight, similar to what has been observed in previous studies [33, 34, 39]. On the experimental day 0, the body weight was 352 ± 24 g and did not differ significantly between the groups (one-way ANOVA, F  = 0.512, p  = 0.61).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Rectal administration of TNBS resulted in the development of clinical symptoms of colitis, which manifested as a decrease in food intake and a decrease in body weight, similar to what has been observed in previous studies [33, 34, 39]. On the experimental day 0, the body weight was 352 ± 24 g and did not differ significantly between the groups (one-way ANOVA, F  = 0.512, p  = 0.61).…”
Section: Resultssupporting
confidence: 85%
“…TNBS-induced colitis in rats has also been used to study effects of gut inflammation on the brain. TNBS administration in rats was shown to induce activation of microglia and cytokine release in the brain [32, 33] and increased expression of intestinal TSPO receptors [40]. Therefore, we selected the TNBS-induced colitis model for this study.…”
Section: Introductionmentioning
confidence: 99%
“…Although these studies demonstrate that epithelial Stat3 activation mediates mucosal protective functions, other evidence suggests that Stat3 hyperactivation may also contribute to inflammation. Indeed, increases in serum IL-6 concentrations and Stat3 hyperactivation were observed in IBD patients, as well as in experimental colitis models (53,54). Likewise, Stat3 is hyperphosphorylated in both colonic epithelial cells and lamina propria mononuclear cells in colitis (55).…”
Section: Discussionmentioning
confidence: 97%
“…In FCDIIb, balloon cells expressed both IL-6 and GFAP. Additional work suggests the expression of IL-6 in neurons of the cerebral cortex and hypothalamus with trinitrobenzene sulfonic acid-induced colitis (Wang et al, 2010). Further work has demonstrated that the combination of neuronal depolarization and activation of IL-1R1 with IL-1β can induce neurons to synthesize and release IL-6 (Juttler et al, 2002; Ringheim et al, 1995; Tsakiri et al, 2008a, b).…”
Section: Discussionmentioning
confidence: 99%